Banten from the 15th to 21st century : glorius achievements upcoming accomplishment - Uka Tjandrasasmita (Center for Research and Development of Religious Literature and Heritage Agency for Research & Development, and Training Departement and Religious Affairs of the Republic of Indonesia, 2016)
shd,1/ws.c.1